The Impact of Gadget Use on Communication and Social Behavior of Children in Kediri City - Siti Amanah; Robingatun (Jurnal Mediakita : Jurnal Komunikasi dan Penyiaran Islam, 2023)
This study describes and analyzes about: (1). the impact of using gadget on the communication behavior of children in Kediri City. (2). the impact of using gadget on the social behavior of children in Kediri City. This research is kind of qualitative descriptive research. It took 32 informants, consist of elementary school students from SD Negeri 8 Ngronggo; SD Plus Ar Rahman ; SDN 5 Ngronggo; SD Plus Sunan Ampel ; and SD Islam Al Huda Kota Kediri. In addition, informants from teachers and parents for supporting information relevant to the focus of this research. We used primary data and secondary data with observation, in-depth interviews and documentation data collection techniques. Data analysis based on Miles and Huberman's interactive data analysis model which includes: data reduction, data presentation and conclusion drawing and verification. The conclutions based on the results of this study: the impact of using gadget on children's communication behavior in Kediri City has had positive and negative impact that majority of children in Kediri City got negative impacts from the use of gadget, including: (1) lack of concentration in learning while at home; (2) often procrastinates include the instructions from their parents; (3) tend to be lazy; (4). feeling bored as an effect of gadget addiction; (5) frequently speaks unkind or disrespectful speech that was imitated from social media. In addition, the positive impacts are (1) increase larger knowledge about technology development; (2) up to date to gadget/technology information; and (3) as the development of learning media to support or be complement on offline activities in the classroom. Based on Lasswell's paradigm, communication is the process of conveying a message by a communicator to a communicant through a medium that causes a certain effect. There are three classifications of effects, the first, cognitive effects when it comes to thoughts or reason, such as ability to increase knowledge and for processing of information and even the development of learning media as a support or complement to offline activities in the classroom. Second, affective effects when it comes to feelings, such as feeling bored caused on unplaying gadgets and lack of concentration on studying at home. Third, the conative effect when it comes to behavior, such as being lazy, procrastinating on commands from their parents, and children say or speak with unkind words easily, disrespectful, and said hasrhly. Meanwhile, the impact of using gadget on the social behavior of children in Kediri City is social changes to the environment and prefers to be alone. These two symptoms are called parasocial relationships in which children dissolve in individualistic conditioning and certainly remove their social interaction that causing themselves were eliminated from their own environment.